Kepuasan Kerja Dipengaruhi Oleh Disiplin Kerja, Komunikasi, Dan Stres Kerja Pada Pegawai Dinas Kesehatan Kota Balikpapan - Aisah, Nurul; Ariani, Misna; Arrywibowo, Imam (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
The purpose of this study is to determine the effect of Motivation, Leadership, and Organizational Culture on Employee Job Satisfaction of PT PELNI (Persero) Balikpapan. The type of research used is quantitative research. The sampling technique in this research is total/census sampling with a sample size of 47 employees of PT PELNI (Persero) Balikpapan. The data collection method is done by distributing questionnaires. This research uses SmartPLS in processing data. The result shows that motivation variable has significant effect on job satisfaction of PT PELNI (Persero) Balikpapan employees. Leadership variable has no significant effect on job satisfaction of PT PELNI (Persero) Balikpapan employees. Organizational culture variable has no significant effect on job satisfaction of PT PELNI (Persero) Balikpapan employees.